System-level analysis of neuroblastoma tumor-initiating cells implicates AURKB as a novel drug target for neuroblastoma - Morozova, O.; Vojvodic, M.; Grinshtein, N.; Hansford, L.; Blakely, K.; Maslova, A.; Hirst, M.; Cezard, T.; Morin, R.; Moore, R.; Smith, K.; Miller, F.; et al. (American Association Cancer Research, 2010)
Purpose: Neuroblastoma (NB) is an aggressive tumor of the developing peripheral nervous system that remains difficult to cure in the advanced stages. The poor prognosis for high-risk NB patients is associated with common disease recurrences that fail to respond to available therapies. NB tumor-initiating cells (TICs), isolated from metastases and primary tumors, may escape treatment and contribute to tumor relapse. New therapies that target the TICs may therefore prevent or treat tumor recurrences. Experimental Design: We undertook a system-level characterization of NB TICs to identify potential drug targets against recurrent NB. We used next-generation RNA sequencing and/or human exon arrays to profile the transcriptomes of 11 NB TIC lines from six NB patients, revealing genes that are highly expressed in the TICs compared with normal neural crest-like cells and unrelated cancer tissues. We used gel-free two-dimensional liquid chromatography coupled to shotgun tandem mass spectrometry to confirm the presence of proteins corresponding to the most abundant TIC-enriched transcripts, thereby providing validation to the gene expression result. Results: Our study revealed that genes in the BRCA1 signaling pathway are frequently misexpressed in NB TICs and implicated Aurora B kinase as a potential drug target for NB therapy. Treatment with a selective AURKB inhibitor was cytotoxic to NB TICs but not to the normal neural crest-like cells. Conclusion: This work provides the first high-resolution system-level analysis of the transcriptomes of 11 primary human NB TICs and identifies a set of candidate NB TIC-enriched transcripts for further development as therapeutic targets. ©2010 AACR.